Foreword: International Dispute Resolution in New Zealand - Butler, Petra (Victoria University of Wellington Law Review, 2015)
This article is the foreword to this issue of the Victoria University of Wellington Law Review (’VUWLR’) containing the New Zealand Law Foundation Dispute Resolution Fellowship Lectures from 2013 to 2015. International dispute resolution is central to New Zealand’s future as a trading nation that has always looked to the wider world, and the yearly international dispute resolution week is now an established part of the yearly legal calendar. This issue of the VUWLR contains innovative and insightful discussions into the world of international arbitration.